Increase the efficiency of the Algerian financial market and review of financial policy: An option to get out of the debt economy - MOKHEFI , Amine; AMRANI , Mohamed (Dirassat Journal Economic Issue, 2016)
The Algerian financial market has grown significantly during recent years. Although some factors limit the scope of its development, the market has become a means of financing that is becoming the channel of choice for better resource allocation. This research aims to present a true reflection of the evolution of Algerian financial market through its compartments , its players and also the various reforms that have been issued . The focus is on boundaries that continue to influence its development.